Influence of icings on river aufeis fluviogenesis - V. R. Alekseev (Лëд и снег)
Formation and development of a river network in the permafrost zone is heavily influenced by icings and icing processes. It is of the most widespread occurrence in regions of discontinuous and continuous permafrost where the mean thickness of the ice on rivers varies over the range 1−2.5 m, and most of the ice cover is formed by consecutive freezing of outcropping groundwater. The intensity of cryogenic channel formation in the permafrost zone has a clearly pronounced cyclic character that depends on the exceeding of the icing ice over the water edge of the river during the autumn low-water period. Five stages of cryogenic channel genesis are described: preglacial, transgressive, stabilizing, regressive, and postglacial. To each stage there corresponds a definite glaciohydrological regime of the discharge channels, their shape, size, and spatial distribution. The channel network is in its maximum development during the third and fourth states when the channel of the allochthonous flow divides into a number of shallow branches producing a complicated plan pattern of the terrain. Mature sites of annual appearance of icings clearly show areas that are in different development stages, which bears witness to a broad range of variability in the channel icing genesis across space and time. According to the size of icings, the flow of the river and geologo-geomorphological and cryogenic-hydrological conditions, five kinds of icing structure of the channel network have been identified: fan-shaped, cone-shaped, treelike, reticular, and longitudinal-insular. The channel icing network is a characteristic indicator of the specific character of development of glaciohydrosystems in the permafrost zone.